2014
DOI: 10.1007/s00018-014-1694-0
|View full text |Cite
|
Sign up to set email alerts
|

Esculentin-1a(1-21)NH2: a frog skin-derived peptide for microbial keratitis

Abstract: Pseudomonas aeruginosa is the primary bacterial pathogen causing contact lens related keratitis. Available ophthalmic agents have reduced efficacy and antimicrobial peptides (AMPs) hold promise as future antibiotics. Here we investigated the in vitro and in vivo anti-Pseudomonal activity of esculentin-1a(1-21)-NH2, derived from a frog skin AMP. The data revealed a minimum inhibitory concentration between 2 and 16 μM against reference strains or drug-resistant clinical isolates of P. aeruginosa without showing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 63 publications
0
50
2
Order By: Relevance
“…The established ability of Esc(1-21) to kill microbes without harming mammalian cells, namely its high anti- Pseudomonal activity also in physiologically relevant conditions [46,51] makes this short-sized AMP a particularly attractive candidate wound healing promoter, especially in the management of chronic, often Pseudomonas -super-infected, human skin ulcers [52,100]. …”
Section: Discussionmentioning
confidence: 99%
“…The established ability of Esc(1-21) to kill microbes without harming mammalian cells, namely its high anti- Pseudomonal activity also in physiologically relevant conditions [46,51] makes this short-sized AMP a particularly attractive candidate wound healing promoter, especially in the management of chronic, often Pseudomonas -super-infected, human skin ulcers [52,100]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, in vivo experiments revealed that Esc(1-21) prolongs survival of murine models of P. aeruginosa-induced sepsis or lung infection, upon intravenous or intra-tracheal administration, respectively . Despite this and other studies showing an in vivo antimicrobial activity of AMPs (Giacometti et al 2006;Pini et al 2010;Uccelletti et al 2010;Xiong et al 2011;Luca et al 2014;Jung Kim et al 2014;Kolar et al 2015), inherent limitations for the development of these molecules as new anti-infective therapeutics include: (1) cytotoxicity outside their natural environment, which can strongly dampen the in vivo antimicrobial efficacy of AMPs, and (2) problems with stability, bioavailability and delivery systems. With reference to the latter, studies on the effect of the incorporation of d-amino acids into AMPs were mainly focused on the antimicrobial activity of the peptides, their reduced cytotoxicity and their increased stability to circulating enzymes (Hamamoto et al 2002;Papo et al 2002).…”
Section: Introductionmentioning
confidence: 96%
“…Note that the treatment approach used is in sharp contrast with standard of care antibiotic regimen for bacterial keratitis in human patients in which drops are administered every 15 min up to 1 h, during the first two days of treatment. In parallel, a 2-4 log reduction in the number of viable Pseudomonas cells was observed in the cornea of peptide-treated eyes compared to the vehicle control, as well as a lower number of recruited inflammatory cells like neutrophils, as determined by the relative myeloperoxidase activity in the harvested corneas [59]. In another set of experiments, prophylactic treatment was done by applying the peptide 3 times in 24 h before inducing keratitis, then the treatment was continued post-infection.…”
Section: In Vivo Efficacy Against Bacterial Infections In Mammalsmentioning
confidence: 86%
“…The two selected esculentin derivatives are endowed with a large spectrum of antibacterial activity encompassing Grampositive and Gram-negative species, including clinical isolates with a different antibiotic susceptibility profile, with MIC values in the range of 1-16 M, with the exception of Staphylococcus aureus strains toward which they are practically inactive [59]. In contrast with the majority of mammalian AMPs [51,52], both esculentin derivatives retain their bactericidal activity at high ionic strength and in the presence of biological fluids e.g.…”
Section: In Vitro Antibacterial Activities Of Esc-1a(1-21)nh 2 and Esmentioning
confidence: 99%
See 1 more Smart Citation